2017
DOI: 10.1186/s13104-017-2627-4
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in a resource-constrained hospital in Madagascar

Abstract: BackgroundStroke is reported as the most frequent cause of in-hospital death in Madagascar. However, no descriptive data on hospitalized stroke patients in the country have been published. In the present study, we sought to investigate the feasibility of collecting data on stroke patients in a resource-constrained hospital in Madagascar. We also aimed to characterize patients hospitalized with stroke.MethodsWe registered socio-demographics, clinical characteristics, and early outcomes of patients admitted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
3
9
0
Order By: Relevance
“…It includes 21 items under four domains of physical/social, pain/emotional, financial stability and environmental domains. Hence it addresses many of the deficiencies of utilizing current QOL measures within the resource-constrained settings [26][27][28][29]31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It includes 21 items under four domains of physical/social, pain/emotional, financial stability and environmental domains. Hence it addresses many of the deficiencies of utilizing current QOL measures within the resource-constrained settings [26][27][28][29]31].…”
Section: Discussionmentioning
confidence: 99%
“…Stroke-related literature is scarce in relation to LMICs. Hence most of the evidence on stroke rehabilitation which come from Western settings which might not be applicable for lower-middle income settings [26][27][28][29][30]. The development of new QOL tools for stroke survivors would enable more context-related QOL measurements [31].…”
Section: Introductionmentioning
confidence: 99%
“…These findings fit with known reported delays in presentation and diagnosis [7] , [8] . It is most likely also what contributes to the reported poor outcome [9] , [10] , [11] . The reported better access to tele-radiology in LMICs were reassuring when considering the significant lack of specialised care.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, until recently many tertiary/referral hospitals in sub Saharan Africa did not have CT scan machines [24,37]. Few stroke persons were opportune to have a CT scan viz: 5.83% 24, 11.11% [62] in Nigeria, 10% from Madagascar [63] and even 0% from Gambia [64]. More recently, the percentages are increasing gradually as one Nigerian study showed that 40.8% patients had CT brain, while 5.6% had magnetic resonance imaging (MRI) [65] and 34.9% in Zimbabwe [60].…”
Section: Action Taken In the Care Of Stroke In Sub Saharan Africamentioning
confidence: 99%
“…Regrettably, some are unaware of the presence of these risk factors or are poorly controlled if know [74]. High blood pressure is the most powerful predictor of stroke, and its treatment can reduce the risk of stroke by ≥ 40% [62]. In one case however, as much as 64% of the stroke patients had the hypertension diagnosed for the first time [29].…”
Section: Recommendationsmentioning
confidence: 99%